The Bed Nucleus of the Stria Terminalis Modulates Learning after Stress in Masculinized But Not Cycling Females - Bangasser, Debbie A. (Society for Neuroscience, 2008)
Exposure to an acute stressful event enhances classical eyeblink conditioning in male rats, but severely impairs conditioning in female rats. Previous studies have demonstrated that the hippocampus and amygdala critically mediate this effect in both sexes. Thus, although stress affects learning in opposite ways, the structures involved are similar. Previously, we found that the bed nucleus of the stria terminalis (BNST) is also necessary for the enhanced learning after stress in male rats. Here we used BNST inactivation to determine whether the BNST, a sexually dimorphic brain region, is required in female rats for the impaired learning after stress. Interestingly, inactivation of the BNST did not prevent the stress-induced impairment of conditioning in females. Thus, unlike the hippocampus and amygdala, the BNST is critically involved in the modulation of learning by stress in males, but not in females. This exclusive involvement in males may be caused by the sex differences within the BNST. These sex differences result from early testosterone exposure, which masculinizes brain regions including the BNST. Previously, we reported that, like males, females with brains that are masculinized at birth learn better after stressful experience. Here we found that the enhanced learning after stress in masculinized females was prevented by BNST inactivation, just like in males. These data suggest that a masculinized BNST is required for the enhanced learning after a stressful experience. Importantly, together these studies indicate that males and females can engage different brain structures to modulate learning after a stressful experience.